Hadith #356 - Sunan al-Nasa'i - Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Aisha bint Abi Bakr; al-Rabi' bin Sulaiman Ø§ÙØ±Ø¨ÙØ¹ Ø¨Ù Ø³ÙÙÙØ§Ù; Bakr bin Madr bin Muhammad Ø¨ÙØ± Ø¨Ù ÙØ¶Ø± Ø¨Ù ÙØÙØ¯; Ishaq bin Bakr bin Madr Ø¥Ø³ØØ§Ù Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØ¶Ø±; Umarh bint 'Abdur Rahman Ø¹ÙØ±Ø© Ø¨ÙØª Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø²Ø±Ø§Ø±Ø© (Sunan al-Nasa'i)
âThat is not menstruation, rather it is a kick in the womb, so let her work out the length of the menses that she used to have, and stop praying (for that period of time), then after that let her perform Ghusl for every for every prayer.â
Grade:

Hadith #391 - Sunan al-Nasa'i - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abdur Rahman bin al-Qasim Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø§ÙÙØ§Ø³Ù Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ±; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Aisha bint Abi Bakr; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Muhammad bin Salmah ÙØÙØ¯ Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¨Ø§ÙÙÙ; Umarh bint 'Abdur Rahman Ø¹ÙØ±Ø© Ø¨ÙØª Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø²Ø±Ø§Ø±Ø© (Sunan al-Nasa'i)
âUmm âAtiyah would never mention the Messenger of Allah (ï·º) without saying: âMay my father be ransomed for him.â I said: âDid you hear the Messenger of Allah (ï·º) say such and such?â And she said: âYes, may my father be ransomed for him.â He said: âLet the mature girls, virgins staying in seclusion, and menstruating woman go out and witness the good occasions and the supplications of the Muslims, but let the menstruating women keep away from the prayer place.'â
Grade:

Hadith #963 - Sunan al-Nasa'i - Abu Bakr bin 'Abdur Rahman Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ´Ø§Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hurairah; Muhammad bin Mansur bin Da'ud ÙØÙØ¯ Ø¨Ù ÙÙØµÙØ± Ø¨Ù Ø¯Ø§ÙØ¯ Ø§ÙØ·ÙØ³Ù; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ©; Umar bin âAbdul-âAziz Ø¹ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ²; Yahya bin Sa'id al-Ansari ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØ£ÙØµØ§Ø±Ù (Sunan al-Nasa'i)
Abu Hurairah (led them in prayer and) recited: âWhen the heaven is split asunder.â and prostrated during it. When he had finished praying, he told them that the Messenger of Allah (ï·º) had prostrated during it.
Grade:

Hadith #1294 - Sunan al-Nasa'i - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hameed al-Sa'idi al-Ansari; al-Harith bin Mskyn bin Muhammad Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ³ÙÙÙ Ø¨Ù ÙØÙØ¯; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ (Sunan al-Nasa'i)
âI asked Zaid bin Kharijah who said: âI asked the Messenger of Allah (ï·º) and he said: Send salah upon me and strive hard in supplication, and say: Alahumma salli âala Muhammad wa âala ali Muhammad (O Allah, send salah upon Muhammad and upon the family of Muhammad).'â
Grade:

Hadith #1505 - Sunan al-Nasa'i - Abbad bin Tameem Mazni; Abdur Rahman bin 'Abdullah bin 'Utba Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ØªØ¨Ø© Ø§ÙÙØ³Ø¹ÙØ¯Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Muhammad bin Mansur bin Da'ud ÙØÙØ¯ Ø¨Ù ÙÙØµÙØ± Ø¨Ù Ø¯Ø§ÙØ¯ Ø§ÙØ·ÙØ³Ù; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ©; Tameem bin Zayd/Ghaziya Mazni (Sunan al-Nasa'i)
âThere was an eclipse of the sun during the time of the Messenger of Allah (ï·º). He stood and prayed, standing for a very long time, then he bowed for a very long time. Then he stood up and (remained standing) for a very long time, but shorter than the first time. Then he bowed for a very long time, but shorter than the first time. Then he prostrated, then he raised his head and stood for a long time, but it was shorter than the first time. The he stood up and (remained standing) for a long t
Grade:

Hadith #1856 - Sunan al-Nasa'i - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Aisha bint Abi Bakr; ibn Umar; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Umarh bint 'Abdur Rahman Ø¹ÙØ±Ø© Ø¨ÙØª Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø²Ø±Ø§Ø±Ø© (Sunan al-Nasa'i)
âDo not wail over me, for no one wailed over the Messenger of Allah.â This is an abridgment.
Grade:

Hadith #2045 - Sunan al-Nasa'i - Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; al-Laith bin Sa'd Ø§ÙÙÙØ« Ø¨Ù Ø³Ø¹Ø¯; Khalid bin Mahran al-Hadha' Ø®Ø§ÙØ¯ Ø¨Ù ÙÙØ±Ø§Ù Ø§ÙØØ°Ø§Ø¡; Muhammad bin 'Abdullah bin 'Abdul Hakam ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØÙÙ; Sa'id bin Abi Hilal Ø³Ø¹ÙØ¯ Ø¨Ù Ø£Ø¨Ù ÙÙØ§Ù Ø§ÙÙÙØ«Ù; Shu'aib bin Abi Hamza Ø´Ø¹ÙØ¨ Ø¨Ù Ø£Ø¨Ù ØÙØ²Ø© (Sunan al-Nasa'i)
when the Messenger of Allah came to the graveyard he would say: âAs-salamu âalaykum ahli ad-diyari min al-muâminin wal-muslimin wa inna I shaâ Allahu bikum lana faratun wa nahnu lakum tabaâun, asâalullahal-âafiyata lana wa lakum. (Peace by upon the inhabitants of this place among the believers and Muslims. Soon we will join you, if Allah willing. You have gone on ahead of us and we will follow you. I ask Allah to keep us and you safe and sound.)â
Grade:

Hadith #3068 - Sunan al-Nasa'i - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; al-Husain bin Hryth Ø§ÙØØ³ÙÙ Ø¨Ù ØØ±ÙØ«; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ© (Sunan al-Nasa'i)
âI saw the Messneger of Allah stone the Jamrat while on his camel saying: âO people, learn your rituals (of Hajj) for I do not know whether I will perform Hajj again after this year.'â
Grade:

Hadith #3069 - Sunan al-Nasa'i - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu al-Badah Ø£Ø¨Ù Ø§ÙØ¨Ø¯Ø§Ø Ø¨Ù Ø¹Ø§ØµÙ Ø¨Ù Ø¹Ø¯Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Amr bin 'Ali bin Bahr al-Bahli Ø¹ÙØ±Ù Ø¨Ù Ø¹ÙÙ Ø¨Ù Ø¨ØØ± Ø§ÙØ¨Ø§ÙÙÙ; Asim bin 'Adiy bin al-Jadd; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan al-Nasa'i)
âThe Messenger of Allah stoned the Jamrat on the Day of Sacrifice in the forenoon, and after the Day of Sacrifice he stoned (the Jamarat) When the sun had passed its zenith.â
Grade:

Hadith #3303 - Sunan al-Nasa'i - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Hisham bin 'Urwa ÙØ´Ø§Ù Ø¨Ù Ø¹Ø±ÙØ©; Muhammad bin 'Ubaid al-Tanafasi ÙØÙØ¯ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø£ÙÙØ© Ø§ÙØ·ÙØ§ÙØ³Ù; Umarh bint 'Abdur Rahman Ø¹ÙØ±Ø© Ø¨ÙØª Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø²Ø±Ø§Ø±Ø© (Sunan al-Nasa'i)
âI read a book to Ash-Shaâbi in which it was narrated from Jabir that the Prophet said: âA woman should not be taken as a co-wife to her paternal aunt or her maternal aunt.â He said: âI heard that from Jabir.'â
Grade:

Hadith #4676 - Sunan al-Nasa'i - Abu Bakr bin 'Abdur Rahman Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ´Ø§Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hurairah; al-Laith bin Sa'd Ø§ÙÙÙØ« Ø¨Ù Ø³Ø¹Ø¯; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Umar bin âAbdul-âAziz Ø¹ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ²; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan al-Nasa'i)
âThe Messenger of Allah forbade the price of a dog, the gift of a female fornicator, and the fee of a fortuneteller.â
Grade:

Hadith #4677 - Sunan al-Nasa'i - Abdur Rahman bin Khalid Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø®Ø§ÙØ¯ Ø¨Ù ÙØ³Ø§ÙØ±; Abu Bakr bin 'Abdur Rahman Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ´Ø§Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Hajjaj bin Muhammad al-Musaysi ØØ¬Ø§Ø¬ Ø¨Ù ÙØÙØ¯ Ø§ÙÙØµÙØµÙ Ø§ÙØ£Ø¹ÙØ±; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Ibrahim bin al-Hasan bin al-Hythm Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø§ÙØØ³Ù Ø¨Ù Ø§ÙÙÙØ«Ù; Umar bin âAbdul-âAziz Ø¹ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² (Sunan al-Nasa'i)
âThe Messenger of Allah said â among the things that be forbade â âAnd the price of a dog.â
Grade:

Hadith #4853 - Sunan al-Nasa'i - Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; al-Hakm bin Musa Ø§ÙØÙÙ Ø¨Ù ÙÙØ³Ù Ø§ÙØ¨Ø²Ø§Ø²; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Amr bin Mnswr al-Nsa'iy Ø¹ÙØ±Ù Ø¨Ù ÙÙØµÙØ± Ø§ÙÙØ³Ø§Ø¦Ù Ø£Ø¨Ù Ø³Ø¹ÙØ¯; Muhammad bin 'Amr bin Hazm; Sulaiman bin Da'ud bin Da'ud Ø³ÙÙÙØ§Ù Ø¨Ù Ø¯Ø§ÙØ¯ Ø¨Ù Ø¯Ø§ÙØ¯ Ø¨Ù Ø¹ÙÙ; Yahya bin Hamza bin Waqd ÙØÙÙ Ø¨Ù ØÙØ²Ø© Ø¨Ù ÙØ§ÙØ¯ (Sunan al-Nasa'i)
âFor fingers (the Diyah is ) ten (camels) each.
Grade:

Hadith #4854 - Sunan al-Nasa'i - Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; al-Hythm bin Mrwan bin al-Hythm Ø§ÙÙÙØ«Ù Ø¨Ù ÙØ±ÙØ§Ù Ø¨Ù Ø§ÙÙÙØ«Ù; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Muhammad bin 'Amr bin Hazm; Muhammad bin Bkar bin Bilal ÙØÙØ¯ Ø¨Ù Ø¨ÙØ§Ø± Ø¨Ù Ø¨ÙØ§Ù Ø§ÙØ¹Ø§ÙÙÙ; Sulaiman bin Arqm Ø³ÙÙÙØ§Ù Ø¨Ù Ø£Ø±ÙÙ; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan al-Nasa'i)
âFingers are the same, (the Diyah is) ten (camel).
Grade:

Hadith #4857 - Sunan al-Nasa'i - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; al-Harith bin Mskyn bin Muhammad Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ³ÙÙÙ Ø¨Ù ÙØÙØ¯; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ± (Sunan al-Nasa'i)
âthis and this are the same,â: meaning the little finger and the thumb.
Grade:

Hadith #2121 - Sunan Abi Dawud - Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Muhammad bin Abi Bakr bin Muhammad ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Umm Salamah; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù; Zuhayr bin Harb Ø²ÙÙØ± Ø¨Ù ØØ±Ø¨ Ø¨Ù Ø´Ø¯Ø§Ø¯ Ø£Ø¨Ù Ø®Ø«ÙÙØ© (Sunan Abi Dawud)
The Messenger of Allah (ï·º) married me when I was seven years old. The narrator Sulaiman said: or Six years. He had intercourse with me when I was nine years old.
Grade: Sahih

Hadith #3518 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ³ÙÙØ© Ø¨Ù ÙØ¹ÙØ¨ Ø§ÙÙØ¹ÙØ¨Ù; Abu Bakr bin 'Abdur Rahman Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ´Ø§Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hurairah; Abu Ja'far al-Nafaili Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØÙØ¯ Ø£Ø¨Ù Ø¬Ø¹ÙØ± Ø§ÙÙÙÙÙÙ Ø§ÙØØ±Ø§Ù; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Umar bin âAbdul-âAziz Ø¹ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ²; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
The Prophet (ï·º) said: The neighbour is most entitled to the right of pre-emption, and he should wait for its exercise even if he is absent, when the two properties have one road.
Grade: Sahih

Hadith #3595 - Sunan Abi Dawud - Abdullah bin 'Amr bin 'Uthman Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù Ø¹Ø«ÙØ§Ù Ø§ÙÙØ·Ø±Ù; Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abdullah bin Wahb Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ¨ Ø¨Ù ÙØ³ÙÙ Ø§ÙÙØ±Ø´Ù; Abdur Rahman bin Abi 'Amra; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Ahmed bin Sa'id bin Sakhar Ø£ØÙØ¯ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ØµØ®Ø±; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
âKaâb!â He said: âAt your service, Messenger of Allah.â Thereupon he made a gesture with is hand indicating: Remit half the debt due to you. Kaâb said: âI shall do so, Messenger of Allah.â The Prophet (ï·º) then said: âGet up and dischargeâ
Grade: Sahih

Hadith #954 - Jami' al-Tirmidhi - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Muhammad bin Yahya bin Abi 'Umar ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹ÙØ± Ø§ÙØ¹Ø¯ÙÙ; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ© (Jami' al-Tirmidhi)
Umar bin Ubaidullah bin Maâmar was complaining about his eyes while he was a Muhrim. He asked Aban bin Uthman about it and he said: âBandage it with some aloes, for I heard Uthman bin Affan mentioning that the Messenger of Allah said: âBandage it with aloes.'â
Grade:

Hadith #955 - Jami' al-Tirmidhi - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abdur-Razzaq Ø¹Ø¨Ø¯ Ø§ÙØ±Ø²Ø§Ù Ø¨Ù ÙÙØ§Ù; Abu al-Badah Ø£Ø¨Ù Ø§ÙØ¨Ø¯Ø§Ø Ø¨Ù Ø¹Ø§ØµÙ Ø¨Ù Ø¹Ø¯Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; al-Hasan bin 'Ali al-Halwani Ø§ÙØØ³Ù Ø¨Ù Ø¹ÙÙ Ø§ÙØ®ÙØ§Ù Ø§ÙØÙÙØ§ÙÙ; Asim bin 'Adiy bin al-Jadd; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ± (Jami' al-Tirmidhi)
The Prophet passed by him while he was at Al-Hudaibiyah, before entering Makkah, and he was a Muhrim. He had lit a fire under a cooking pot and lice were falling all over his face. So he (the Prophet) said: âHave these lice of yours troubled you?â He said: âYes.â He said: âShave and feed six of the poor with a Faraqâ and a Faraq is three Sa â âor fast three days, or slaughter a sacrifice.â Ibn Abi Najih (one of the narrators) said: âOr slaughter a sheep.â
Grade:

Hadith #1004 - Jami' al-Tirmidhi - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Aisha bint Abi Bakr; ibn Umar; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Ishaq bin Musa bin 'Abdullah bin Musa Ø¥Ø³ØØ§Ù Ø¨Ù ÙÙØ³Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ³Ù; Ma'n bin 'Isa bin Yahya ÙØ¹Ù Ø¨Ù Ø¹ÙØ³Ù Ø¨Ù ÙØÙÙ; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Umarh bint 'Abdur Rahman Ø¹ÙØ±Ø© Ø¨ÙØª Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø²Ø±Ø§Ø±Ø© (Jami' al-Tirmidhi)
The Prophet said: âThe deceased is punished for the crying of his family over him.â So, Aishah said: âMay Allah have mercy upon him. He has not lied, but he is mistaken. It is only that the Messenger of Allah said about a Jewish man who died: âThe deceased is being punished and his family is crying over him.'â
Grade:

Hadith #1258 - Jami' al-Tirmidhi - Abu Bakr bin 'Abdur Rahman Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ´Ø§Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hurairah; al-Laith bin Sa'd Ø§ÙÙÙØ« Ø¨Ù Ø³Ø¹Ø¯; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Umar bin âAbdul-âAziz Ø¹ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ²; Yahya bin Sa'id al-Ansari ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØ£ÙØµØ§Ø±Ù (Jami' al-Tirmidhi)
That the Messenger of Allah (ï·º): âA riding animal can be ridden while it is pawned, and a milking animal can be milked while it is pawned, and it is up to the one riding and drinking (the milk) to maintain it.â This Hadith is Hasan Sahih. We do now know of it being Marfuâ except by the narration of âAmir Ash-Shaâbi from Abu Hurairah. Others have reported this Hadith from Al-Aâmash, from Abu Salih, from Abu Hurairah in Mawquf form. This is acted upon according to some of the people
Grade:

Hadith #1322 - Jami' al-Tirmidhi - Abdur-Razzaq Ø¹Ø¨Ø¯ Ø§ÙØ±Ø²Ø§Ù Ø¨Ù ÙÙØ§Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hurairah; Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ; al-Husain bin Mhdy bin Malik Ø§ÙØØ³ÙÙ Ø¨Ù ÙÙØ¯Ù Ø¨Ù ÙØ§ÙÙ; Ma'mar bin Rashid ÙØ¹ÙØ± Ø¨Ù Ø±Ø§Ø´Ø¯; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Yahya bin Sa'id al-Ansari ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØ£ÙØµØ§Ø±Ù (Jami' al-Tirmidhi)
That the Messenger of Allah (ï·º) passed by a pile of food. He put his fingers in it and felt wetness. He said: âO owner of the food! What is this ?â He replied: âIt was rained upon O Messenger of Allah.â He said: âWhy not put it on top of the food so the people can see it?â Then he said: âWhoever cheats, he is not one of us.'â He said: There are narrations on this topic from Ibn âUmar, Abu Al-Hamraâ, Ibn âAbbas, Buraidah, Abu Burdah bin Niyar, and Hudhaifah bin Al-Yaman.
Grade:

Hadith #2002 - Jami' al-Tirmidhi - Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Aisha bint Abi Bakr; al-Laith bin Sa'd Ø§ÙÙÙØ« Ø¨Ù Ø³Ø¹Ø¯; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Umarh bint 'Abdur Rahman Ø¹ÙØ±Ø© Ø¨ÙØª Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø²Ø±Ø§Ø±Ø©; Yahya bin Sa'id al-Ansari ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØ£ÙØµØ§Ø±Ù (Jami' al-Tirmidhi)
âA man shall remain exalting himself until he is written among the tyrants, so that he suffers from their afflictions.â
Grade:

Hadith #2394 - Jami' al-Tirmidhi - Abdullah bin 'Amr bin 'Uthman Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù Ø¹Ø«ÙØ§Ù Ø§ÙÙØ·Ø±Ù; Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Ma'n bin 'Isa bin Yahya ÙØ¹Ù Ø¨Ù Ø¹ÙØ³Ù Ø¨Ù ÙØÙÙ; Muhammad bin 'Abdullah al-Ansari ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø§ÙÙØ«ÙÙ - Ø§ÙØ£ÙØµØ§Ø±Ù; Zayd bin Khalid al-Juhni (Jami' al-Tirmidhi)
âThe Messenger of Allah(s.a.w) ordered us to throw dut in the mouths of those who praise others.â
Grade:

Hadith #2396 - Jami' al-Tirmidhi - Abdullah bin 'Amr bin 'Uthman Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù Ø¹Ø«ÙØ§Ù Ø§ÙÙØ·Ø±Ù; Abdur Rahman bin Abi 'Amra; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Bashr bin Adam al-Dareer Ø¨Ø´Ø± Ø¨Ù Ø¢Ø¯Ù Ø§ÙØ¶Ø±ÙØ±; Kharija ibn Zayd ibn Thabit Ø®Ø§Ø±Ø¬Ø© Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø«Ø§Ø¨Øª Ø§ÙØ£ÙØµØ§Ø±Ù; Zayd bin al-Habab al-'Akli Ø²ÙØ¯ Ø¨Ù Ø§ÙØØ¨Ø§Ø¨ Ø£Ø¨Ù Ø§ÙØØ³ÙÙ Ø§ÙØ¹ÙÙÙ; Zayd bin Khalid al-Juhni (Jami' al-Tirmidhi)
âWhen Allah wants good for his slave, He hastens his punishment in the world. And when He wants bad for His slave, He withholds his sins from him until he appears before Him on the Day of Judgement.â And with this (same) chain, (it was reported) from the Prophet (ï·º) who said: âIndeed greater reward comes with greater trial. And indeed, when Allah loves a people He subjects them to trials, so whoever is content, then for him is pleasure, and whoever is discontent, then for him is wrath.â
Grade:

Hadith #958 - Sunan Ibn Majah - Abdul Malik bin 'Abdul 'Aziz bin 'Abdul Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hameed al-Sa'idi al-Ansari; Amar bin Talwt bin 'Aabad Ø¹ÙØ§Ø± Ø¨Ù Ø·Ø§ÙÙØª Ø¨Ù Ø¹Ø¨Ø§Ø¯ Ø§ÙØ¬ØØ¯Ø±Ù; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ± (Sunan Ibn Majah)
âI saw the Prophet (ï·º) performing prayer while sitting on his right side when he was sick.â
Grade:

Hadith #1112 - Sunan Ibn Majah - Abu Bakr bin 'Abdur Rahman Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø§ÙØØ§Ø±Ø« Ø¨Ù ÙØ´Ø§Ù; Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Abu Hurairah; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ©; Umar bin âAbdul-âAziz Ø¹ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ²; Yahya bin Sa'id al-Ansari ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØ£ÙØµØ§Ø±Ù (Sunan Ibn Majah)
âI asked the Messenger of Allah (ï·º): âWhich is better prayer in my house or prayer in the mosque?â He said: âDo you not see how close my house is to the mosque?â But praying in my house is dearer to me than praying in the mosque, apart from the prescribed prayers.ââ
Grade:

Hadith #1326 - Sunan Ibn Majah - Abbad bin Tameem Mazni; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Muhammad bin al-Sabah ÙØÙØ¯ Ø¨Ù Ø§ÙØµØ¨Ø§Ø Ø§ÙØ¨Ø²Ø§Ø² Ø§ÙØ¯ÙÙØ§Ø¨Ù; Sufyan bin 'Uyaynah Ø³ÙÙØ§Ù Ø¨Ù Ø¹ÙÙÙØ©; Yahya bin Sa'id al-Ansari ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø§ÙØ£ÙØµØ§Ø±Ù (Sunan Ibn Majah)
âThe Messenger of Allah (ï·º) forbade eulogies.â
Grade:

Hadith #1424 - Sunan Ibn Majah - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abdullah bin Qays bin Makhrama; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Zayd bin Khalid al-Juhni (Sunan Ibn Majah)
âThere are people who fast and get nothing from their fast except hunger, and there are those who pray and get nothing from their prayer but a sleepless night.â
Grade:

Hadith #1669 - Sunan Ibn Majah - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Khalid bin Mukhallad al-Qatwani Ø®Ø§ÙØ¯ Ø¨Ù ÙØ®ÙØ¯ Ø§ÙÙØ·ÙØ§ÙÙ (Sunan Ibn Majah)
âThe Massenger of Allah cursed the Muhallil and the Muhallal lahu.â
Grade:

Hadith #1992 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Muhammad bin Abi Bakr bin Muhammad ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Umm Salamah; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Ibn Majah)
âI heard him meaning Ibn âAbbas allowing exchange (of Dirhams for Dirham etc., if extra was given) and that was narrated from him. Then I heard that he has taken back this opinion. I met him in Makkah and said: âI heard that you had taken back (your opinion).â He said: âYes. That was just my own opinion, but Abu Saâeed narrated from the Messenger of Allah (ï·º) that he forbade exchange (of like items if extra is given).ââ
Grade:

Hadith #2068 - Sunan Ibn Majah - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; al-'Aswad bin 'Amir Shadhan Ø§ÙØ£Ø³ÙØ¯ Ø¨Ù Ø¹Ø§ÙØ± Ø´Ø§Ø°Ø§Ù; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; Zuhayr bin Mua'wiya bin Hudayj Ø²ÙÙØ± Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø¨Ù ØØ¯ÙØ¬ (Sunan Ibn Majah)
âThe Prophet (ï·º) was with one of the Mothers of the Believers (his wives) and another (wife) sent a bowl containing food. She (the first wife) struck the hand of the Messenger of (ï·º) and the bowl fell and broke. The Messenger of Allah (ï·º) took the two pieces and put them back together, then he started gathering up the food and putting it in (the bowl). He said: âYour mother was jealous. Eat.â So they ate, and she (the wife who broke the bowl) brought the bowl that was in her house an
Grade:

Hadith #3151 - Sunan Ibn Majah - Abdullah bin Abi Bakr bin Muh. b. 'Amr Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù; Abdur Rahman bin Mahdi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙØ¯Ù; Abdur-Razzaq Ø¹Ø¨Ø¯ Ø§ÙØ±Ø²Ø§Ù Ø¨Ù ÙÙØ§Ù; Abu al-Badah Ø£Ø¨Ù Ø§ÙØ¨Ø¯Ø§Ø Ø¨Ù Ø¹Ø§ØµÙ Ø¨Ù Ø¹Ø¯Ù; Abu Bakr bin Muhammad bin 'Amr bin Hazm Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹ÙØ±Ù Ø¨Ù ØØ²Ù; Ahmed bin Snan bin Asad Ø£ØÙØ¯ Ø¨Ù Ø³ÙØ§Ù Ø¨Ù Ø£Ø³Ø¯; Asim bin 'Adiy bin al-Jadd; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù (Sunan Ibn Majah)
It was narrated from Ibn âAbbas that the Prophet (ï·º) drank, and took two breaths while doing so.
Grade: